Corrupción y la categoría “delito de cuello blanco”: cuando los delitos se cometen en contextos normalizados - Zúñiga Rodríguez, Laura (2019)
In this article, the author discusses economic crimes and argues that corporative spaces create contexts where white collar crimes are normalized. The concept of “white collar crime” is further analyzed, as well as the problems that their prosecution must face, such as a culture that values power and money, the lack of a social conscience of the harmful consequences of this type of crimes and the lack of information in mass media.